2016
DOI: 10.4236/jtr.2016.43013
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Induced Hypothyroidism during Anti-Tuberculosis Treatment of Multidrug-Resistant Tuberculosis: Notes from the Field

Abstract: We followed 188 euthyroidic persons undergoing treatment for multidrug resistant tuberculosis (MDR-TB) in the state of Karnataka, India to determine the incidence of hypothyroidism during anti-tuberculosis treatment. Overall, among MDR-TB patients with valid thyroid stimulating hormone (TSH) values, about 23% developed hypothyroidism (TSH value ≥10 mIU/ml) during anti-tuberculosis treatment; the majority (74%) occurring after 3 months of treatment. Among 133 patients who received a regimen that contained ethio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 9 publications
2
15
0
2
Order By: Relevance
“…The reported incidence of hypothyroidism in MDR‐TB patients varies greatly from 4% to 69% (Table ). To date, studies have largely investigated the incidence of overt hypothyroidism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The reported incidence of hypothyroidism in MDR‐TB patients varies greatly from 4% to 69% (Table ). To date, studies have largely investigated the incidence of overt hypothyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, despite subnormal thyroid hormone levels, TSH levels in our group of participants were not grossly elevated, raising the possibility that non‐specific chronic illness‐associated central suppression of the thyroid axis may have moderated the degree of TSH elevation. A full literature search using MEDLINE and the English language from January 1997 to December 2017 using the search terms ‘multidrug resistant’, ‘tuberculosis’ and ‘hypothyroidism’ identified six prospective cohort studies, two retrospective cohort studies and two case reports reporting thionamide/PAS‐treatment based thyroid outcomes (Table ) . The most recent report is a prospective study that investigated 188 euthyroid individuals undergoing treatment for MDR‐TB in the state of Karnataka, India, over a 6‐month period .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…arthralgia, depression, ectodermal dysplasia, psychosis, and xeroderma), and hence may be under-diagnosed. A study in Bangalore reported that prevalence of hypothyroidism during MDR treatment was substantially greater when patients had routine serologic testing as compared to passive detection (23% vs 4%) [33]. Data from this study influenced an update of the guidelines to test every MDR-TB patient for hypothyroidism.…”
Section: Contribution Of or To Policy And Practicementioning
confidence: 97%
“…Compliance with infection control practices in sputum microscopy centres: a study from Kerala, IndiaYes [57]32. Incidence of Drug Induced hypothyroidism during Intensive Phase of treatment for multi drug resistance TB among patients registered under PMDT in Karnataka, IndiaYes [33]33. Will sensitizing qualified private practitioners and Ayurveda medical officers improve symptomatic referral and TB case detection in Bilaspur District, Himachal Pradesh, India?Yes [66]34.…”
Section: Implementation Of Operational Research Training Coursesmentioning
confidence: 99%